"Common fires": a tribute - Robinson, Jack (My University, 2018)
This is a review of Richard Wagamese's 1994 novel Keeper 'n Me and a detailed appreciation of Anishnaabe values as presented in the novel.
Keywords: Canadian fiction; cultural values; Indigenous studies